Government Policy Responses to Financial Crises: Identifying Patterns and Policy Origins in Developing Countries. (April 2015) - Ha, Eunyoung; Kang, Myung-koo
Summary: This paper investigates how three major political conditions—political constraint (imposed by veto players), government partisanship, and elections—have influenced the government responses to financial crises in 98 developing countries over the period 1976–2004. We find that governments experiencing financial crises generally tightened their monetary and fiscal policies, but the extent of the tightening was considerably moderated by the presence of large political constraint (large and strong veto players), strong leftist partisan power in government, and upcoming legislative or presidential elections. We also find that fiscal policies are more considerably constrained by political conditions than monetary policies.